High Intensity Long Interval Sets Provides Similar Enjoyment as Continuous Moderate Intensity Exercise. The Tromsø Exercise Enjoyment Study - Sagelv, Edvard H.; Hammer, Tord; Hamsund, Tommy; Rognmo, Kamilla; Pettersen, Svein Arne; Pedersen, Sigurd (Frontiers in Psychology, 2019)
Objective: High intensity interval exercise sessions with interval sets over 3 minutes may provide superior cardiorespiratory fitness benefits. To our knowledge, the exercise enjoyment of interval sets over 3 minutes is not yet elucidated. The aim of this study was to examine exercise enjoyment following one session with four intervals of 4 minutes high intensity exercise (HIIE) versus one session of 45 minutes moderate intensity continuous exercise (CE) in iso-caloric conditions using a randomized crossover design. Methods: Seven young healthy participants were recruited to undergo two different exercise sessions in a randomized order: 1) 4x4-minute intervals at >90% of maximum heart rate (HRmax) with 3 minutes of rest between interval sets, and 2) 45 minutes continuous exercise at 70% of HRmax. Peak oxygen uptake and HRmax were evaluated prior to the experiment. The participants reported their perceived exercise enjoyment using the 18-item Physical Activity Enjoyment Scale (PACES) questionnaire and their rating of perceived exertion (RPE). Results: There was no difference in the PACES score between the high intensity interval exercise session (median: 95.5 (inter-quartile range: 21.8)) and the moderate intensity continuous exercise session (91.0 (13.5), p=0.36, r=-0.22). The participants reported a higher RPE in the high intensity interval exercise session (16.5 (2.0)) compared with the continuous exercise session (9.0 (2.0), p=0.01, r=-0.88). Conclusion: Similar exercise enjoyment was reported following four high intensity intervals of 4 minutes compared with a moderate intensity continuous exercise session in this randomized crossover study with iso-caloric conditions. If enjoyment is a mediating factor for engaging in exercise, one should expect a similar probability of exercise adherence following high intensity 4-minute intervals and continuous moderate intensity exercise when prescribing aerobic exercise as preventive medicine.